Ethics and Bioethics. Bases for Informed Consent in Orthodontics - Virginia Pentón García; Zhenia Véliz Äguila; Bárbara Prado Lemus; Ledys Mary Herrera (Medisur, 2009)
The quality and scientific development of health assistance in Cuba are reflected in its health index which is an expression of respect for all those who give and receive health services in the country. Thus human dignity, which is widely represented in the informed consent should be a premise while practicing a high quality health service according to the principles of Bioethics, constituting it an ethical challenge for all the health staff. This paper reviews the principles of Bioethics with regards to informed consent in Orthodontics.